2002
DOI: 10.1128/mcb.22.22.7942-7952.2002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding of the β1 Adrenergic Receptor to the Cyclic AMP-Dependent Guanine Nucleotide Exchange Factor CNrasGEF Leads to Ras Activation

Abstract: G-protein-coupled receptors (GPCRs) can indirectly activate Ras primarily through the ␤␥ subunits of G proteins, which recruit c-Src, phosphatidylinositol 3-kinase, and Grb2-SOS. However, a direct interaction between a Ras activator (guanine nucleotide exchange factor [GEF]) and GPCRs that leads to Ras activation has never been demonstrated. We report here a novel mechanism for a direct GPCR-mediated Ras activation. The ␤1 adrenergic receptor (␤1-AR) binds to the PDZ domain of the cyclic AMP (cAMP)-dependent R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…In keeping, we show that NE and E are able to elicit activation of p42/p44 and p38 MAPKs, acknowledged to have mandatory roles for cell growth, survival and invasive ability, in both primary and metastatic cell lines. This observation is in agreement with the findings of Pak et al, 23 also indicating the Ras-MAPKs pathway as a target of b-adrenoceptors. These data could be of striking interest in order to find new strategies for melanoma treatment.…”
Section: Discussionsupporting
confidence: 83%
“…In keeping, we show that NE and E are able to elicit activation of p42/p44 and p38 MAPKs, acknowledged to have mandatory roles for cell growth, survival and invasive ability, in both primary and metastatic cell lines. This observation is in agreement with the findings of Pak et al, 23 also indicating the Ras-MAPKs pathway as a target of b-adrenoceptors. These data could be of striking interest in order to find new strategies for melanoma treatment.…”
Section: Discussionsupporting
confidence: 83%
“…The intracellular domains of several GPCRs have been shown to bind to proteins that might function as alternative GPCR signal transducers, among which include GEFs for small G proteins, nonreceptor tyrosine kinases, and several proteins that function as adaptors or scaffolds. A specific peptide motif in the C terminus of the ␤ 1 -adrenergic receptor binds directly to the postsynaptic density protein of 95 kDa/ disc-large/zona occludens-1 (PDZ) domain of the cAMP-regulated Ras GEF (cyclic nucleotide-Ras GEF), allowing the receptor to stimulate guanine nucleotide exchange on the small G protein Ras (Pak et al, 2002). Another PDZ domaincontaining protein, the Na ϩ /H ϩ exchanger regulatory factor/ ezrin binding protein 50, binds to the C terminus of ␤ 2 -adrenergic and parathyroid hormone/parathyroid hormonerelated protein receptors and confers the ability to regulate Na ϩ /H ϩ exchanger 3 activity (Hall et al, 1998;Mahon et al, 2002).…”
Section: Gpcr Coupling To Non-g Protein Effectorsmentioning
confidence: 99%
“…We and others have previously identified a guanine nucleotide exchange factor, called CNrasGEF (also known as PDZ-GEF1, nRapGEF, RA-GEF, and RAPGEF2) (20 -23). Our previous work showed that when expressed heterologously in HEK293T cells, CNras-GEF can activate Ras in response to elevation of cAMP levels (independent of protein kinase A), achieved by treatment with 8-Br-cAMP or forskolin plus IBMX (20) or by agonist (isoproterenol) stimulation of co-expressed b1 adrenergic receptor, a G protein-coupled receptor that activates G␣ s and leads to elevation of intracellular cAMP levels (24). CNrasGEF can also activate Rap1, independent of cAMP (20 -23).…”
mentioning
confidence: 99%